Myocardial function and effects of biologic therapy in patients with severe psoriasis: a prospective echocardiographic study. (6th April 2015) - Ahlehoff, O.; Hansen, P.R.; Gislason, G.H.; Frydland, M.; Bryld, L.E.; Elming, H.; Jemec, G.B.E.
Abstract: Background: Psoriasis is a chronic inflammatory disease and is associated with cardiovascular events. Little is known about subclinical myocardial dysfunction and potential changes in myocardial function during anti‐inflammatory treatment in these patients. We prospectively studied left ventricular function in patients with severe psoriasis who initiated biologic therapy. Methods: Between November 1 2013 and May 31 2014 the study subjects underwent physical, laboratory and comprehensive echocardiographic examination at baseline and after 3 months of treatment. Pearson correlation coefficients and Student's t ‐test were applied to assess changes in diastolic function (defined as the E/e' ratio) and global longitudinal strain (GLS). Results: Eighteen patients with severe psoriasis treated with biologic therapy with a mean follow‐up of 85.6 ± 18.2 days were included. The patients had a baseline psoriasis area and severity index (PASI) of 12.0 ± 4.1 and normal left ventricular ejection fraction [(LVEF) 56.3 ± 3.8%], diastolic dysfunction (E/e′ 8.1 ± 2.1) and GLS (−16.8 ± 2.1%). At follow‐up, an improvement (baseline vs. follow‐up) of PASI (12.0 ± 4.1 vs. 2.7 ± 3.1, P < 0.001), E/e′ (8.1 ± 2.1 vs. 6.7 ± 1.9, P ≤ 0.001) and GLS (−16.8 ± 2.1 vs. −18.3 ± 2.3%, P < 0.001) were recorded. No changes were demonstrated in LVEF (56.3 ± 3.8 vs. 56.8 ± 3.3%, P = 0.31), body mass index (30.9 ± 5.7 vs. 31.0 ± 5.8 kg/m 2, P = 0.90), mean arterial blood pressure (103.1 ± 8.5 vs. 103.7 ± 10.8 mmHg, P = 0.74). Likewise, no changes were seen in total cholesterol, low density lipoprotein cholesterol, high density lipoprotein cholesterol, estimated glomerular filtration rate and glycosylated haemoglobin. Conclusion: In patients with severe psoriasis treatment with biologic therapy was associated with improved PASI and amelioration of myocardial dysfunction.